Evaluation of genetic variants in microRNA biosynthesis genes and risk of breast cancer in Chinese women. Issue 9 (11th July 2013) - Jiang, Yue; Chen, Jiaping; Wu, Jiangping; Hu, Zhibin; Qin, Zhenzhen; Liu, Xiao'an; Guan, Xiaoxiang; Wang, Yanru; Han, Jing; Jiang, Tao; Jin, Guangfu; Zhang, Mingfeng; et al.
Abstract : MicroRNAs (miRNA) are a class of small, noncoding RNA molecules involved in a diversity of cellular functions. Single nucleotide polymorphisms (SNPs) in miRNA biosynthesis genes may affect the biogenesis of miRNAs and consequently affect the miRNAs regulation. In this study, we systematically selected 24 functional SNPs located in eight key biosynthesis genes of miRNA ( DROSHA, DGCR8, RAN, DICER, AGO2, GEMIN3, GEMIN4 and HIWI ) and investigated the association between these SNPs and the risk of breast cancer in a Chinese population. All 24 SNPs were firstly genotyped in stage 1 (878 cases and 900 controls) and three promising SNPs ( DROSHA rs2291109, RAN rs7301722 and DGCR8 rs417309) were selected for further validation in stage 2 (914 cases and 967 controls). We found that only one SNP (rs417309) located in the 3′‐UTR of DGCR8 was consistently associated with an increased breast cancer risk in two stages with a combined odds ratio (OR) of 1.50 [95% confidence interval (CI) = 1.16–1.93]. Based on the bioinformatics prediction, rs417309 is located at the binding sites of miR‐106b and miR‐579 in the 3′‐UTR of DGCR8 . To evaluate whether rs417309 variant affects the binding capacity of miRNAs, we cotransfected luciferase reporter plasmids of DGCR8 3′‐UTR and miR‐106b/miR‐579 in three cell lines. Luciferase activity assay showed a higher expression level with rs417309 A allele compared with G allele in MCF‐7 cell lines ( p = 3.31 × 10 –7, 9.29 × 10 –7 for miR‐106b and miR‐579, respectively). Our findings suggested that DGCR8 rs417309 G > A might affect breast cancer risk through the interruption of miRNA binding. Abstract : What's new? The existence of single nucleotide polymorphisms (SNPs) in genes involved in the biogenesis of microRNAs (miRNAs) has raised intriguing questions about the relationship between cancer risk and variation within miRNA target sites. Here, a SNP (rs417309) identified in the 3′‐UTR of an miRNA biosynthesis gene known as DGCR8 was associated with an increased risk of breast cancer in a Chinese population and, based on bioinformatics analyses, has a predicted location at the binding sites of miR‐106b and miR‐579. Luciferase reporter activity suggests that rs417309 G>A might affect breast cancer risk through the interruption of miRNA binding.